HUBUNGAN TINGKAT KEBISINGAN KERJA TERHADAP GANGGUAN PENDENGARAN PADA PEKERJA DI PABRIK PTPN 7 KABUPATEN SELUMA - ikhwan, arie; Yolanda Manda Sari, Aprilia (Poltekkes Kemenkes Bengkulu, 2021)
Problems found in PTPN 7 Factory Seluma Regency in the rubber processing section In the production process using mechanical equipment that causes sounds that cause noise and have an adverse impact on health, safety and comfort work because the intensity of the noise exceeds 85 dB continuously can cause temporary hearing loss and can even cause deaf people. The purpose of the study was to determine the relationship between noise level and hearing loss at the Seluma Regency PTPN 7 Factory. The research method used is descriptive analytical method with cross sectional approach observation. The results of the study were that most workers experienced severe hearing loss with a noise level> 85 as many as 40 workers 71.4% had exceeded the Threshold Value while <85 as many as 16 workers 28.6% had no hearing loss with noise level. Audiometry instrument examination results from 56 PTPN 7 factory workers in the rubber processing section showed 16.1% Normal, 12.5% ​​Mild, 14.3% Medium, 57.1% Weight. With the Chi-Square statistical test, the value of ρ Value = 0,000 (ρ value <0.05) means that there is a relationship between the Noise Level and hearing loss of workers at the Seluma Regency PTPN 7 Factory. PTPN 7 Factory. Management is expected to be able to use the information from this research to reduce the risk of noise/hearing loss effects on workers.